Enhanced magnetic irreversibility characteristics by expansion of blocking block for Sr2Ca2Cu3O8−δ high-Tc superconductor. (5th July 2017) - Aoba, Tomoya; Suzuki, Tsuneo; Nakayama, Tadachika; Suematsu, Hisayuki; Niihara, Koichi; Karppinen, Maarit
Abstract: We demonstrate that the irreversibility field characteristics of high- T c superconductors are not necessarily enhanced by decreasing the thickness of the non-superconducting blocking block between adjacent superconducting blocks. The experimental data are for the high-pressure-synthesized Sr2 Ca2 Cu3 O8−δ (0 (Sr) 223; T c = 105 K) phase and for its water-containing derivative phase (H2 O) m /2 Sr2 Ca2 Cu3 O8−δ (H- m (Sr) 223; T c = 105 K), which spontaneously forms when the 0 (Sr) 223 phase is exposed to air at 80 °C. Our results clearly show that the insertion of water into the 0 (Sr) 223 phase expands the blocking block by 3.1 Å along the c -axis but improves the J c and H irr properties while keeping the high T c intact.